Facile synthesis of 3D hierarchical mesoporous Fe-C-N catalysts as efficient electrocatalysts for oxygen reduction reaction. (8th March 2018) - Liu, Sa; Yang, Zheng; Li, Mengli; Lv, Wenjie; Liu, Liwen; Wang, Yan; Chen, Xiaowen; Zhao, Xinsheng; Zhu, Ping; Wang, Guoxiang
Abstract: A salt crystal-templating synthesis route is proposed to synthesize a Fe-N-C catalyst with well-controlled mesoporous structure. In the presence of glucose, NaCl-template can efficiently tune the porous structure of catalyst and help to improve the oxygen reduction reaction (ORR) activity. The optimized catalyst possesses a hierarchical mesopore size distribution, a high Brunauer-Emmett-Teller surface area (up to 911.56 m 2  g −1 ) and homogeneous distribution of abundant active sites. As a result, the obtained catalyst shows a desirable ORR activity in alkaline medium (half-wave potential of 0.84 V and kinetic mass activity at 0.8 V of 24.95 A g −1 ), high selectivity (electron transfer number >3.92), excellent long term durability (only 16 mV negative shift of half-wave potential after 5000 potential cycles in O2 -saturated 0.1 M KOH) and good tolerance to methanol. The enhanced electrochemical performance enables the proposed catalyst to be the promising electrocatalyst candidate to commercial Pt/C towards ORR. Graphical abstract: A 3D hierarchical mesoporous Fe-C-N catalyst with a large surface area was proposed as efficient electrocatalysts for oxygen reduction reaction by an eco-friendly and facile "salt crystal-templating" synthesis route. Highlights: A 3D hierarchical porous Fe-N-C catalyst is synthesized by an eco-friendly route. Catalysts show a large specific area (911.56 m 2  g −1 ) and abundant active sites. Hierarchical porous structure efficiently facilitates mass transfer during ORR. As-prepared catalyst shows excellent ORR activity and stability in alkaline media.